Collaborative Governance in The Development of Mangrove Rehabilitation in Cigorondong Village Sumur District Pandeglang Regency - Stiawati, Titi; Nuraeni, Munawaroh (Future Science, 2024)
Indonesia has the largest mangrove environment in the world. The government itself has launched a national mangrove rehabilitation initiative of 600.000 hectares, in accordance with the 2020-2024 RPJMN through low carbon development. Banten Province is one of the provinces in Indonesia that has experienced environmental degradation, so that the existing mangrove ecosystem area is not comparable to the potential mangrove habitat that should be. The government, communities, and businesses have adopted various initiatives and programs in the form of rehabilitation projects that aim to rebuild damaged mangrove forests and establish mangrove centers. Therefore, this study aims to determine collaborative governance in the development of mangrove rehabilitation in Cigorondong Village, Sumur District, Pandeglang Regency. By using indicators in Ansell and Gash's collaborative governance model (2007), where the actors involved are government, private, academics and non-governmental organizations. This research uses descriptive method with qualitative approach. The results showed that the collaboration that occurred was quite successful in being well implemented with the rehabilitated mangrove area